PERBANDINGAN RISIKO PASAR (BETA SAHAM) PADA 9 SEKTOR PERUSAHAAN DI PASAR MODAL - Aghnia, Hurin; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to identify the effects of market risk (stock beta) across nine sectors of companies in capital market on the return produced during the Covid-19 pandemic in Indonesia in the short and the long term. This quantitative research uses two variables: stock returns in composite index obtained from idx.co.id as the dependent variable and market risk (stock beta) and the index of the nine sectors as the independent variables. The results of the analysis indicate that four hypotheses were proven in the long term; they are agricultural sector, basic industry sector, consumption goods sector, and property sector. The said finding indicates that, during the Covid-19 pandemic, anytime the stock price and the market risk increase, the stock return of the composite index will drop. Hence, when the stock price and the market risk of those sector rise, the number of investors buying the four sectoral stock will decrease. In the short term, three hypotheses were accepted; they are in agricultural sector, basic industry sector, and consumption goods sector. During the Covid-19 pandemic, any increase in the sectors’ stock price and market risk will be followed by a decline in the composite index’s return because when the stock price and market risk increase, the number of investors